Organizational performance and time management: The Nigerian context - Opiah Ayaokpo Alex (YAYASAN MITRA PERSADA NUSANTARA, 2026)
The ability to manage time is an ever-important skill that managers in organizations should master and effectively apply in the day to day running of official operations. Mastering this skill is essential for employee performance, efficiency, and organizational productivity. This paper discusses time management and how it effects the way organizations perform, behave and function in Nigeria. It examines how cultural perceptions of time influence time and how it shapes organizational performance, employee behavior, and productivity. It reveals that organizations are faced with time management problems, which have become a burden towards an effective performance and service delivery. Through participant observation methodology and the application of the contingency theory, it is recommended, amongst others, that organizations and government take into cognizance Nigeria’s unique, diverse socio-cultural environment and support employees’ autonomy, relatedness, and competence through effective leadership styles to promote time management and organizational performance and also enact policies in accordance with specific regional prevailing circumstances.